A qualitative study of the practice‐related decision‐making of Intensive Interaction Practitioners. (6th November 2020) - Firth, Graham; Glyde, Megan; Denby, Gemma
Accessible summary: People who use Intensive Interaction want to find the best ways to enjoy interacting with people with learning disabilities and/or autism. This study is about how the people who use Intensive Interaction (in this study called "practitioners") decide how best to do it, often as they go along. This study found that the practitioners who use Intensive Interaction with people with learning disabilities and/or autism think about a lot of different things. They think about some things before they start doing Intensive Interaction with a person, other things while they are doing the Intensive Interaction and some more things when they have finished. The study also says that the practitioners who use Intensive Interaction could do it even better if they thought about it more or watched some video of their Intensive Interactions, either on their own or with the help of some other people who also do Intensive Interaction. Abstract: Background: This study looked to investigate the sometimes conscious and sometimes intuitive decision‐making processes of Intensive Interaction practitioners. More specifically, this study set out to develop a rich description of how practitioners make judgements when developing a dynamic repertoire of Intensive Interaction strategies with people with severe or profound learning difficulties and/or autism, how this decision‐making process is enacted in practice and what issues inform such decisions. Materials and Methods: This research followed a "Template Analysis" qualitative methodology, informed by semi‐structured interviews with 13 experienced Intensive Interaction Practitioners (who had completed the Intensive Interaction Coordinators course as administered by the Intensive Interaction Institute). The participants included the following: speech and language therapists, parents, teachers, residential care staff and managers, and a clinical psychologist. Results: The findings of this study indicate why and how certain decisions are made by experienced practitioners before, during and after engagement in Intensive Interaction. Such decision‐making is indicated as sometimes being intuitive in nature, sometimes more conscious, sometimes moving between the two cognitive states as differing issues arise. Practitioner decision‐making was focused on a number of issues, including specific learning or care "agendas"; practitioner confidence and knowledge; environmental considerations; individual learner characteristics and behaviour; learner attention, "attunement" and arousal levels; building a shared "repertoire"; and issues of available time. Conclusions: The issue of how novice Intensive Interaction practitioners may best be supported to more quickly and confidently develop improved Intensive Interaction practices is discussed, proposing the development of a cyclical process of experiential learning and supported reflection.